Self-healing of asphalt mastic using capsules containing waste oils - Yamac, Ozge Erdogan; Yilmaz, Mehmet; Yalcin, Erkut; Kok, Baha Vural; Norambuena-Contreras, Jose; Garcia, Alvaro (Elsevier Sci Ltd, 2021)
Several capsules were prepared using two different waste oils (vegetable oils and mineral oils), five different oil/water ratios, and four different amounts of sodium alginate as a polymer matrix. Capsules with waste oils were characterized by physical, thermal, and mechanical properties to define the more effective capsule for asphalt self-healing purposes. The capsules were added in ratios of 0.25%, 0.50%, 0.75%, and 1.0% by total weight of mastic. The crack-healing efficiency of the optimum capsules was evaluated at two different curing temperatures (25 degrees C and 40 degrees C) on asphalt mastic samples using three-point bending tests. The main results proved that capsules could survive the mixing and compacting processes and releasing the encapsulated waste oils inside them by the action of mechanical loads. 100 ml water, 500 ml waste oil, and 17.5 gr sodium alginate were found to be the optimum capsule content for both types of oils. An increased rate of water/oil resulted in decreased free compressive strength. It was further detected that the self-healing levels of asphalt mastic samples with capsules demonstrated 80% higher healing levels compared to samples without capsules and the level of self-healing depended on the ratio of capsules added into the mixtures and the curing temperature applied. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Self-healing capability; Asphalt mastic; Capsules; Waste vegetable oil; Waste mineral oil